2016
DOI: 10.1186/s13102-016-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in exercise capacity, muscle strength, and health-related quality of life in esophageal cancer patients undergoing esophagectomy

Abstract: BackgroundSurgery for cancer of the thoracic esophagus is a challenging procedure associated with high morbidity and mortality. Perioperative rehabilitation has been introduced to promote early mobilization of the patients and to prevent postoperative pulmonary complications. The purpose of the present study was to characterize the preoperative functional exercise capacity, muscle strength, anxiety, depression, and health-related quality of life (QOL) in patients with esophageal cancer, and to evaluate the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…Previous studies have shown the beneficial effects of interventions based on ERAS guidelines to improve the nutrition and physical status of patients with head, neck, and breast cancer after surgery [ 12 , 13 ]. For patients with esophageal cancer, existing interventions may be effective, but each intervention program usually focuses on one specific aspect of health such as nutrition or exercise [ 14 - 16 ]. To meet different needs, such as overcome postoperative complications and malnutrition, patients need to meet different professionals and to return to the hospital frequently for different appointments, creating potential obstacles for those who have been discharged from the hospital, especially those residing in rural or remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the beneficial effects of interventions based on ERAS guidelines to improve the nutrition and physical status of patients with head, neck, and breast cancer after surgery [ 12 , 13 ]. For patients with esophageal cancer, existing interventions may be effective, but each intervention program usually focuses on one specific aspect of health such as nutrition or exercise [ 14 - 16 ]. To meet different needs, such as overcome postoperative complications and malnutrition, patients need to meet different professionals and to return to the hospital frequently for different appointments, creating potential obstacles for those who have been discharged from the hospital, especially those residing in rural or remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this longitudinal study was the first to find that both current non-smoker status and handgrip strength could predict recovery from a poor health status, measured with the CAT. Previous cross-sectional studies have identified these two determinants, but separately [7,20,21,22,23,24,25,26,27]. For example, Martínez et al found that CAT scores greater than 10 points identified subjects that were current smokers or had smoked in the past [20].…”
Section: Discussionmentioning
confidence: 99%
“…They found a strong relationship between COPD exacerbation frequency and that domain, which is related to the activities of daily life that require handgrip strength [25]. Similarly, Inoue et al found that the CAT score was inversely associated with handgrip strength [26]. It is well known that muscle dysfunction (muscular atrophy and weakness) is a recognized feature of COPD [27]; muscle dysfunction leads to inactivity, and consequently, a worse perception of health status and a negative prognosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nasogastric drainage of the gastric conduit is maintained in the first postoperative days. Early mobilization of patients prevents lung complications, influences muscle strength, anxiety and quality of life of the patient (57). Hemo-dynamic monitoring and blood oximetry are very important after esophagectomy.…”
Section: Postoperative Periodmentioning
confidence: 99%